Frekuensi Pemberian Pakan Limbah Carica (Vasconcellea pubescens A.DC) terhadap Perkembangan Larva Black Soldier Fly (Hermetia illucens L.) - Nuranisah, Annanda; Ambarningrum, Trisnowati Budi; Atang, Atang; Haryanto, Trisno; Setiyono, Eko (Fakultas Biologi Universitas Jenderal Soedirman, 2022)
Carica (Vasconcellea pubescens A.DC) waste in Wonosobo can be a problem. Black Soldier Fly/ BSF (Hermetia illucens L.) is biodegradator insect can be right solution. BSF able to convert organic waste into nutrients for growth and development. The purpose of this study was to determine the effectiveness of the frequency of feeding carica industrial waste on the development of BSF larvae, to determine the effect of feeding frequency on the increase in larval biomass and to determine the survival rate of BSF larvae. The study used an experimental method with RAL factorial. The first factor is type of feed, carica and chicken pellets. Frequency of feeding as the second factor is the frequency of once a day, every two days and three days. Variable of the experiment is head capsule, number of prepupae larvae, larval biomass and survival rate. The data obtained were analyzed by ANOVA at an accuracy level of 95%, if it had a significant effect, it would be continued with the DMRT test. The results of the study The frequency of feeding both once a day (F1), twice a day (F2), and every three days (F3) had no effect on the development of BSF larvae (P> 0.05). The frequency of feeding affects biomass of larvae, the frequency of feeding every day (F1) has the highest biomass while the mechanism of feeding frequency every three days (F3), although given the same quantity of feed weight per day has the lowest biomass. The survival rate of carica feeding is lower, which is about 60-70% at the three different frequencies with chicken pellet feeding which still reaches 90% in each treatment.